(untitled) (Research, Society and Development, 2020)
With the emergence of the new Covid-19 disease in Brazil in the beginning of 2020, many companies had to reduce their activities or even paralyze them completely, another part of these companies had an additional demand compared to the daily history of operation. The objective of this article is to understand and analyze the main difficulties in the IT field of three large companies to adapt their ICT infrastructure to the new scenario under the theoretical lenses of the Theory of Dynamic Capacities and Theory of Adaptive Structuring. The methodology of this research project proposes the study of multiple cases with a longitudinal perspective and the Dynamic Capabilities Research Model and the Technology Appropriation Model with an exploratory approach, through a case study. As a result, the two models prove that companies A, B and C were able to meet the new demands, adapting their ICT infrastructures to the new scenario caused by the Covid-19 pandemic, forcing employees to adopt the new form of work.